ENVIRONMENTAL ASPECTS OF THE USE OF SCRAP IN STEEL PRODUCTION - S. V. Korneev; S. M. Kabishov (Литьë и металлургия)
The article shows the major environmental problems arising from the use of scrap in steelmaking. Presented conditions appearance in the electric furnace emissions of harmful substances and their control measures. Shown the advantages of a preliminary preparation and cleaning impurities of metal as one of the measures to reduce emissions from the furnaces into the atmosphere.